2015
DOI: 10.1016/j.biomaterials.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of long-acting folic acid-receptor targeted ritonavir-boosted atazanavir nanoformulations

Abstract: Long-acting nanoformulated antiretroviral therapy (nanoART) that target monocyte-macrophage could improve the drug’s half-life and protein binding capacities while facilitating cell and tissue depots. To this end, ART nanoparticles that target the folic acid (FA) receptor and permit cell-based drug depots were examined using pharmacokinetic and pharmacodynamic (PD) tests. FA receptor-targeted poloxamer 407 nanocrystals, containing ritonavir-boosted atazanavir (ATV/r), significantly affected several therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 46 publications
3
57
0
Order By: Relevance
“…There are various combination nanoformulations that have been reported (7,8,12,(25)(26)(27)(28)(29). Freeling et al produced solid lipid nanoparticles containing boosted lopinavir (L/r) and TFV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various combination nanoformulations that have been reported (7,8,12,(25)(26)(27)(28)(29). Freeling et al produced solid lipid nanoparticles containing boosted lopinavir (L/r) and TFV.…”
Section: Discussionmentioning
confidence: 99%
“…Using macaque model, the investigators demonstrated enhanced penetration of the ARV drugs into lymph nodes compared to that of free drugs (10,27). Other investigators have used wet-milled technique to develop FTC crystals that boosted protease inhibitor efficacy in humanized mice when linked with folic acid (28,29). Recently, the LATTE-2 study, administering long-acting cabotegravir and rilpivirine intramuscularly every 2 months or every month, has announced positive results (30).…”
Section: Discussionmentioning
confidence: 99%
“…The present study on FA-nanoATV/r treated NSG mice builds on prior PK and PD studies. The promising results lay a foundation to further develop nanoformulations for clinical use(Puligujja et al, 2015). …”
mentioning
confidence: 99%
“…18,19 This, taken together, makes FA conjugation suitable for MP targeting of ARV nanoparticles (nanoformulated antiretroviral therapy [nanoART]) for treatment of HIV-1 infection. 18,19 In particular, PK and pharmacodynamics (PD) studies have demonstrated that such targeting strategies improve drug biodistribution. However, efficacy determinations have entailed intensive tissue drug chemical analyses.…”
Section: Et Almentioning
confidence: 99%
“…However, efficacy determinations have entailed intensive tissue drug chemical analyses. 18,20 We posit that testing of targeting ligands can be sped by MRI evaluation of magnetite-labeled ARV particle tissue distributions.…”
Section: Et Almentioning
confidence: 99%